AN ANALYSIS OF TRANSLATION OF CULTURAL WORDSIN MEYER'S NOVEL TWILIGHT - Yayang Mia Lestiani, - (2009)
ABSTRACT This research paper is entitled An Analysis of Translation of Cultural Words in Meyer's Novel Twilight. The aims of the study are to investigate the types of cultural words discovered in the novel and to investigate the translation procedures used by the translator in translating the cultural words into Indonesian. A qualitative method was applied in this study. This method allowed the writer to make a systematic and factual description of the obtained data. The data were all the cultural words discovered in the novel and a hundred of them were taken purposively. The data were categorized based on Newmark's categories of cultural words (1988) namely ecology, material, social, and organization. The findings of the study show that material was the most frequent category of cultural words found in the novel. The translation procedures used were those which were proposed by Newmark (1988); transference, transposition, naturalization, cultural equivalent, componential, through-translation, literal, notes, addition, and glosses, couplet, and reduction. Transference is the most frequent procedure used in translating the cultural words found in the novel.